Antimicrobial Effects of Conditioned Medium From Amniotic Progenitor Cells in vitro and in vivo: Toward Tissue Regenerative Therapies for Bovine Mastitis - Lange-Consiglio, Anna; Gusmara, Claudia; Manfredi, Emanuela; Idda, Antonella; Soggiu, Alessio; Greco, Viviana; Bonizzi, Luigi; Cremonesi, Fausto; Zecconi, Alfonso (Frontiers in Veterinary Science, 2019)
There is increasing evidence to suggest that, in addition to their regenerative effect, mesenchymal stromal cells (MSCs) and their secretome have an anti-inflammatory and antimicrobial roles in the innate immune response in conditions such as sepsis. However, there is no published information on the effect of MSCs in bovine mastitis. Mastitis often results in extensive tissue damage due to multi-microorganism co-infection. This study investigated the ability of amniotic derived conditioned medium (CM), in vitro and in vivo, to counteract microbial action and restore healthy tissue capable of milk production. Following determination of a dose response curve, 10000 colony forming units (CFU) of Staphylococcus aureus (S. aureus) were inoculated into bovine mammary epithelial cell culture with and without 10% CM (supplemented either at the time of bacteria inoculation or after 4h). Acridine orange staining was used to assess cell viability/apoptosis. Additionally, an in vivo study was performed using 48 dairy cows with acute and chronic mastitis, treated with CM (treated group) or antibiotics (control group). In vitro results showed that CM can attenuate bacterial growth, as evaluated by number of CFU. After 24 h of culture with S. aureus, 89.67% of mammary epithelial cells treated with CM were still alive whereas all cells cultured without CM were dead. Rates of epithelial cell survival (60.67%) were similar when CM was added four hours after bacteria inoculation. There was no difference in somatic cell count between cases of acute mastitis in the CM treated or control group in the in vivo study. However, relapses in chronic mastitis were less common in the group receiving CM. Our results show that CM is able to mitigate bacterial growth in vitro and may be particularly useful in the treatment of chronic mastitis, aiding restoration of milk production in cows that would otherwise be removed from the production cycle.